Role of recombinant human granulocyte colony-stimulating factor in development of cancer-associated venous thromboembolism in lung cancer patients who undergo chemotherapy - Cheng, Yi; Zhao, Yunfeng; Xu, Mei; Du, He; Sun, Jinyuan; Yao, Qihuan; Qu, Jianmin; Liu, Song; Guo, Xuejun; Xiong, Wei (Frontiers in Immunology, 2024)
Background The role of recombinant human granulocyte colony-stimulating factor (rhG-CSF) especially long-acting one in the development of cancer-associated venous thromboembolism (VTE) among lung cancer patients who undergo chemotherapy has been understudied, although use of rhG-CSF has been reported to be associated with increased risk of VTE. Methods We retrospectively reviewed 1673 lung cancer patients who underwent hospitalized chemotherapy. We performed propensity score matching to offset confounding factors related to cancer-associated VTE development, and classified them into short-acting (N=273), long-acting (N=273), and no rhG-CSF (N=273) groups. The primary outcome was the cumulative cancer-associated VTE development three months after all cycles of chemotherapy. Results The overall VTE incidence were 5.5%, 10.3%, and 2.2% in the short-acting, long-acting, and no rhG-CSF groups, respectively (P<0.001). The VTE incidence in the long-acting rhG-CSF group was higher than that in the short-acting (P=0.039) and no rhG-CSF groups (P<0.001), respectively. The VTE incidence in the short-acting rhG-CSF group was higher than that in the no rhG-CSF group (P=0.045). The use of rhG-CSF (hazard ratio [HR] 2.337, 95% confidence interval [CI] [1.236-5.251], P=0.006) were positively correlated with the VTE development among all the patients, whereas the use of long-acting rhG-CSF (HR 1.917, 95% CI [1.138-4.359], P=0.016), were positively correlated with the VTE development among the patients receiving rhG-CSF. Conclusions Use of rhG-CSF especially long-acting rhG-CSF increases the risk of cancer-associated VTE development compared with no rhG-CSF use in lung cancer patients who undergo hospitalized chemotherapy.